Propuesta y ventaja técnica comparativa de una galga para inspección visual en juntas soldadas - Anastasio Dominguez, Julio Cesar (2023)
A device for visual inspection in welded joints has been proposed, the research was oriented to demonstrate the technical advantage over conventional instruments. For this purpose, inspections were planned on standard welded specimens with the proposed device and the Cambridge, Fillet Weld, Hi-Lo, Adjustable Fillet Weld, Skew - T Fillet and Automatic Weld Size gauges. The experimental results have shown that the useful instrument, due to its geometric arrangement, presents a technical advantage with respect to the gauges studied. In fillet welding, the instrument sizes the leg and throat size in a single welding step, in groove welding the reinforcement size verification is convenient and fast, also checking the joint bevel angle, and misalignment after of the assembly. The demonstrated technical advantage has allowed the patent to be registered at INDECOPI.